Cabaran Dan Peranan Pembuat Kraf Dalam Pelestarian Budaya Benda Masyarakat Orang Ulu Di Belaga Sarawak (Craftmakers' Challenges And Roles In Sustaining Material Culture Among The Orang Ulu In Belaga Sarawak - Faridah, Sahari; Anna, Durin; Spencer Empading, Sanggin (UM Press, 2016)
Orang Ulu is comprised of many ethnic groups; Kayan, Kenyah, Bhukat, and Penan. These groups were known for fine craft makers in the past. They took advantage for the diverse species of natural construction materials such as rattan, Pandanus, bamboo, and donax within their environment to produce a range of craft objects. Modern lifestyle and changing livelihood influence Orang Ulu’s needs and the necessity for materials. Traditional objects are seemed impractical and redundant to their contemporary subsistence and socio-economic activities, religion practice and global trend and taste. On the other hand, the changing of the physical landscape due to development projects in the region has caused a scarcity of construction materials, both in quantity and diversity. All of these factors affect the traditional craft-making activities and have become the main challenge for the Orang Ulu craft makers to sustain their tradition and heritage. This paper discusses the roles and challenges faced by the Orang Ulu’s craft makers in their effort to sustain the craft-making activities and traditional material objects among the Kayan, Kenyah Badeng, Bhukat and Penan communities in the Sg. Asap resettlement scheme of Belaga. Different approaches and strategies were adopted by the craft makers within the individual community to overcome the adversities.